Mental health education: An intervention on stigma on help-seeking behavior among adolescents - Liguid, Maria Junnah Acma; Cuartero, Sunshine Ramilo (Insight: Jurnal Ilmiah Psikologi, 2022)
Mental health concerns confront the youth today, but the self and social stigma of seeking help hinder them from getting help. It is hypothesized in this study that providing mental health education among adolescents can reduce both their self and social stigma of help-seeking behavior. Eighty (80) grade 10 students participated in an intervention study where half of the participants attended a four-session, interactive mental health education. In contrast, the other half attended a similar four-session interactive activity, but topics included inner values of the self which are not related to mental health care. Participants answered two scales, the Self-Stigma of Seeking Help (SSOSH) by Vogel et al. (2006) and Social Stigma for Receiving Psychological Help (SSRPH) by Komiya et al (2000) one week before intervention and two weeks after intervention. Results showed a decrease in both self–stigma and social stigma of help-seeking behavior among those who received a mental health education intervention but not among those who received inner self values education. A significant difference between scores of the two groups in both self and social stigma was also observed. Results of this study imply the importance of incorporating mental health education in the curriculum of the youth to reduce stigma and encourage the young to seek help in times of mental health needs. Keywords: mental health education, stigma, help-seeking behavior